Ambivalent sexism experienced by the female characters in Cho Nam Joo’s Saha - Afifah, Elhama Najihatul; Istiadah, Istiadah (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2025)
This study examines the two subcategories of ambivalent sexism, hostile and benevolent. As they are experienced by the female characters in Cho Nam Joo's Saha. The study investigates how sexism is portrayed in character conversation, actions, and narrative descriptions using a qualitative text analysis method. The ambivalent sexism theory, which was created by Susan Fiske and Peter Glick, was used to analyze the data. Results show that benevolent sexism takes the form of overly protective attitudes and exaggerated praise, while hostile sexism in the book takes the form of verbal and physical abuse. Both of these behaviors reinforce social inequalities and gender stereotypes. The research concludes that Saha effectively portrays the complex dynamics of sexism in a patriarchal society, providing insight into how such themes contribute to discussions on gender studies and literature.